A meta-analysis of tumor necrosis factor (TNF) gene polymorphism and susceptibility to influenza A (H1N1). (December 2020) - Li, Yong; Chen, Xue-Yu; Gu, Wei-Min; Qian, Hai-Ming; Tian, Yuan; Tang, Jie; Cheng, Ting
Graphical abstract: Highlights: A total of 5 eligible studies with 474 cases and 805 controls were included. There were statistically significant for rs361525 in allelic model (A vs. G). There were statistically significant for rs1800750 in dominant model (AA + GA vs. GG). Caucasian with A site mutation of rs361525 was more susceptible to influenza A (H1N1). Abstract: Purpose: The aim of the study was to comprehensively evaluate the associations between tumor necrosis factor (TNF) gene polymorphism and influenza A (H1N1) susceptibility. Methods: The relevant studies were identified through a search of PubMed, Embase, and Cochrane library database until February 29, 2020, without language restrictions. Two independent reviewers extracted the data, and any discrepancies were resolved by consensus. The quality of the eligible article was evaluated by Newcastle-Ottawa Quality Assessment Scale (NOS). Egger's test was applied to evaluate publication bias. All these analyses were performed using Stata15.1 software. Results: A total of 5 studies with 474 cases and 805 controls were included. The results of meta-analysis showed that there were statistically significant for rs361525 in allelic model (A vs. G) [OR = 2.46 (1.10, 5.52)] and for rs1800750 in dominant model (AA + GA vs. GG) [OR = 2.42 (1.24, 4.71)] in cases vs. controls. Furthermore, subgroup analysis for race showed that for rs361525 in allelic model (A vs. G), there were significant differences for Caucasian [OR = 3.64 (1.18, 11.23)] and no significant difference for Mexican [OR = 2.25 (0.82, 6.13)] in cases vs. controls. There was publication bias for rs361525 in dominant model (AA + GA vs. GG, p = 0.042) and rs1800629 in recessive model (AA vs. GG + GA, p < 0.001). Conclusions: Caucasian with A site mutation of -238TNF G/A (rs361525) was more susceptible to influenza A (H1N1).The -376 dominant model AA + GA of TNF genes was associated with the susceptibility to influenza A (H1N1). However, more studies with large sample size are needed to confirm the results.